Facile construction of C3N4-TE@TiO2/UiO-66 with double Z-scheme structure as high performance photocatalyst for degradation of tetracycline. Issue 2 (15th January 2021) - Safaralizadeh, Elnaz; Mahjoub, Ali Reza; Fazlali, Farnaz; Bagheri, Hasan
Abstract: In the current research, a double Z-scheme photocatalyst C3 N4 -TE@TiO2 /UiO-66 (CNTU) is fabricated via a two-steps facile solvothermal method from Z-scheme C3 N4 -TE@TiO2 (CNT). This double Z-scheme photocatalyst reveals greater performance for the removal of tetracycline (TC) than pristine C3 N4 -TE, TiO2, UiO-66 (U66), and their binary compounds. The optimized composite 35C3 N4 -TE@TiO2 /35UiO-66 (35CNTU), exhibitions photocatalytic performance for antibiotic removal (TC) more than 5, 4 and 2 times higher than that pure TiO2, UiO-66, and C3 N4 -TE, respectively. The physical and chemical features of synthesized samples were described via FTIR, XRD, SEM-EDX, TEM, BET, UV–Vis DRS, and PL. The key parameters on photocatalytic performances of 35CNTU such as pH, the amount of catalyst, and the primary concentration of TC were clariﬁed. The advancement of the photocatalytic process for 35CNTU is due to the increase in the surface area and structure of double Z-scheme in this compound, which growths the active sites of the reaction as well as better separation of the photo-induced electron and hole pairs. Furthermore, 35CNTU can be recycled with superior stability for 5 cycles. The photocatalytic removal proficiency of TC over 35CNTU under visible light achieves 96% in 40 min. The findings of this study could inspire various novel plans for fabricating practical double Z-scheme photocatalyst for great performance and extensive useful applications.